A systematic review of the implementation of recommended psychological interventions for schizophrenia: Rates, barriers, and improvement strategies. (5th November 2015) - Ince, Paul; Haddock, Gillian; Tai, Sara
Abstract : Purpose: A systematic review of the literature exploring if the UK recommendations for psychological interventions for schizophrenia were being met was carried out. Rates of implementation for cognitive behavioural therapy (CBT) and family intervention (FI) were compared. The barriers against implementation and described strategies aimed at improving implementation were reviewed. Methods: A literature search of electronic bibliography databases ( Psychinfo, Medline, Pubmed, AMED, CINHAL, and EMBASE ), reference and citation lists, the Evaluation and Review of NICE Implementation (ERNIE) database, a manual search of Clinical Psychology Forum, governmental reports, charity, and service user group reports was conducted. Results: Twenty‐six articles met the inclusion criteria, 11 provided data on implementation rates, 13 explored the barriers to implementation, and 10 gave information about improvement strategies. Rates of implementation varied from 4% to 100% for CBT and 0% to 53% for FI, and studies varied in the methodology used and quality of the articles. Previously reported barriers to implementation were found, with organisational barriers being most commonly followed by barriers met by staff members and service users. Implementation strategies discovered included training packages for CBT, FI, and psychosocial interventions as well as empirical evidence suggesting methods for engagement with service users. Conclusions: Rates of implementation for CBT and FI are still below recommended levels with wide variation of rates found. This suggests inequalities in the provision of psychological interventions for schizophrenia are still present. Previously identified barriers to implementation were confirmed. Attempted implementation strategies have been met with modest success. Practitioner points: Inequalities in the provision of psychological therapies for schizophrenia persist. Good quality cognitive behavioural therapy and FI training do not ensure implementation. Collaboration at all levels of healthcare is needed for effective implementation.